Pengaruh Penambahan Daun Stevia (Stevia rebaudiana Bertoni) terhadap Karakteristik Teh Celup Herbal Temu Putih (Curcuma zedoaria (Berg.) Roscoe) - Kezia br Sinuhaji, Astria; Darmayanti, Luh Putu Trisna; Yusasrini, Ni Luh Ari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 3 (2023): Jurnal ITEPA, 2023)
The objective of this study was to know the effect of stevia leaves addition on the characteristics of herbal tea bag made from white turmeric and to know the right of stevia leaves addition to get the best characteristics of herbal tea bag of white turmeric. This research used a Completely Randomized Design with the stevia leaves addition as a treatment which consist of 6 levels: 0%, 2%. 4%, 6%, 8%, and 10%. The treatment was repeated three times, resulting in 18 experimental units. The data obtained were analyzed by analysis of variance (ANOVA) and if the treatment had a significant effect, then it was followed by The Duncan Multiple Range Test (DMRT). The results showed that the stevia leaves addition had a highly significant effect (P<0,01) on the moisture content, total phenolics, antioxidant activity, and taste (scoring test), had a significant effect (P<0,05) on the ash content, and no significant effect (P>0,05) on panelists’ preference for color, taste, flavor, and overall acceptance.. The result showed that 10% concentration of stevia leaves addition was the best treatment, where the herbal tea produced had a criteria: moisture content 10.58%; ash content 7.14%; total phenolics 17.84 mg GAE/g; powder antioxidant activity 85.94%; brewed antioxidant activity 81.85%; the color, flavor, taste, and an overall acceptance were slightly liked; and the taste was sweet.